2019
DOI: 10.3390/ijms20030468
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Expression of CXCR4 Targets Cardioprotective Vesicles to Myocardial Infarction and Improves Outcome after Systemic Administration

Abstract: Cell therapy has been evaluated to enhance heart function after injury. Delivered cells mostly act via paracrine mechanisms, including secreted growth factors, cytokines, and vesicles, such as exosomes (Exo). Intramyocardial injection of cardiac-resident progenitor cells (CPC)-derived Exo reduced scarring and improved cardiac function after myocardial infarction in rats. Here, we explore a clinically relevant approach to enhance the homing process to cardiomyocytes (CM), which is crucial for therapeutic effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 45 publications
2
71
0
1
Order By: Relevance
“…However, little has been done about the distribution pattern of primed EVs in inflamed colon of murine model. Some studies have shown that EVs generated from priming stem cells reach more damaged tissues, increasing the protection effect 37 . However, unlike other studies, this study demonstrated that similar amount of primed EVs and naïve EVs have been found in colon, and that primed EVs is very effective in mitigating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, little has been done about the distribution pattern of primed EVs in inflamed colon of murine model. Some studies have shown that EVs generated from priming stem cells reach more damaged tissues, increasing the protection effect 37 . However, unlike other studies, this study demonstrated that similar amount of primed EVs and naïve EVs have been found in colon, and that primed EVs is very effective in mitigating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The surface protein defined as pregnancy-associated plasma protein-A (PAPP-A) was found to be associated within CPC-EV as master regulator responsible for the release of active IGF factor leading to activation of pro-survival pathways involving phosphorylation of ERK1/2 and Akt in recipient cells [155]. In a preclinical rat model of acute myocardial infarction (MI), CPC-EVs injected into the infarct border zone or systemically injected via tail vein increased viable mass and vessel density, resulted in a diminished scar and improved global heart function [154,156]. Ibrahim et al showed that CDC-EVs were enriched in miRNA146a-5p.…”
Section: A Role For Cpc-derived Evsmentioning
confidence: 99%
“…Several studies have been lately reported suggesting alternative strategies to functionalise EVs for more accurate targeting of the damaged heart [220,221]. These include: lentiviral vector-based engineering of secreting cells to upregulate the expression of cardiomyocyte-specific binding peptides fused to the murine transmembrane protein Lamp2b, in order to enrich the targeting epitope on the exosomal surface [222]; overexpression of exosomal CXCR4 to push their bioavailability towards the ischaemic heart [156]; membrane anchoring systems to directly dock tissue-specific antibodies or homing antigens on the EV surface [223,224].…”
Section: Looking For the Right Address: Improving Ev Cardiac Tropismmentioning
confidence: 99%
“…Exosome‐producing cells can be molecularly engineered to enrich the presence of specific molecules on the exosome surface in order to target damaged myocardium. Exosomes derived from CPCs engineered to overexpress CXCR4, a receptor of the chemokine stromal cell‐derived factor 1 (SDF‐1), increase myocardium homing and cardioprotective effects in a rat model of ischaemia/reperfusion injury after systemic delivery . The enrichment in ligands can also be achieved by directly conjugating a synthetic myocardium targeting peptide, such as the cardiac homing peptide (CHP), to the surface of intravenously infused CSC‐derived exosomes .…”
Section: Stem Cell Vulnerability Requires a Smooth Deliverymentioning
confidence: 99%
“…Exosomes derived from CPCs engineered to overexpress CXCR4, a receptor of the chemokine stromal cell-derived factor 1 (SDF-1), increase myocardium homing and cardioprotective effects in a rat model of ischaemia/reperfusion injury after systemic delivery. 125 The enrichment in ligands can also be achieved by directly conjugating a synthetic myocardium targeting peptide, such as the cardiac homing peptide (CHP), to the surface of intravenously infused CSC-derived exosomes. 126 In addition, cells labelled with superparamagnetic nanoparticle can be guided to the injury site by an external magnetic field placed above the heart during the injection enhancing the retention/engraftment in the damaged area and multiplying the therapeutic benefit.…”
Section: S Tem Cell V Ulner Ab Ilit Y Requ Ire S a S Mooth Deliverymentioning
confidence: 99%